Thriving Amidst the Pandemic: Examining the Lived Experiences of Work from Home Filipino Teachers - Agnes G. del Rosario; Cynthia P. Galang (International Journal of Social Learning (IJSL), 2021)
The purpose of this study is to investigate the mental, physical, emotional, social, and spiritual experiences of work-from-home (WFH) Filipino teachers. It also provides descriptions of the positive and negative aspects of working from home and how they adapt to the new culture. This study describes exceptional or new thoughts and feelings of WFH Filipino teachers. Using a qualitative phenomenological methodology, the researchers explored teachers’ lived experiences in teaching in a work-from-home environment. This study included ten (10) teachers from both public and private schools in Metro Manila. Analyses of the data revealed key themes from the teachers’ perspectives of the work-from-home environment. Respondents accepted the new culture of working from home, opened their minds to all possibilities, and were eager to learn new things to adapt to changes. Online teaching-learning is not possible without the respondents' participation in training and seminars. Technical issues, communication concerns, student learning conditions, family concerns, household issues, and health conditions are some of the challenges in teaching and working at home based on the research. Teacher participants expressed that WFH experiences were challenging and exhausting but they found it fulfilling as well. They cultivated the teachers’ traits of being flexible, innovative, dynamic, and sociable despite the many challenges that they have encountered in the intricate setup to enhance success and effectiveness in the teaching and learning process.